Aplikasi Pemesanan Tiket Di Wisata Alam Tranding Camp Menggunakan Metode Periodic Review System Berbasis Android - Alfachry, Louliq Rifky; Muhamad Alda (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The rapid development of information and communication technology has brought significant changes in the tourism sector. One of the innovations that has developed is the use of an android application-based information system to facilitate access to information and needs more quickly, practically and precisely. One that needs it is Tranding Camp. Tranding Camp is one of the natural tourist attractions located in North Sumatra where ticket purchases there still use manual methods without the help of technology. This is certainly less effective, if there are many visitors who come, there will be a queue and of course this limits the ability of ticket managers to monitor ticket inventory and make timely decisions. This study builds an android-based ticket booking application using the Periodic Review System method. The Periodic Review System method is able to solve these problems by calculating predictions to manage ticket inventory efficiently in a certain period. The application built is android-based, this application aims to make it easier for visitors to buy tickets and assist managers in stock management. The results of the study showed an increase in operational efficiency and ticket management at Tranding Camp, supporting the use of information technology to improve the quality of tourism services. From the results of testing carried out with a blackbox testing approach, the system that was built can run well.